Verify that the exponetial matrix mapping [C] = e^(-phi*[e_tilde])does have the finite form given in this equation:[C] = e^(-phi*[e_tilde]) = [I_3x3]cos(phi) - sin(phi)*[e_tilde]+(1-cos(phi))*e-hat*e-hat^Twhere [e_tilde] and [gamma_tilde] is a skew symmetric matrix and [e_tilde]^3 = -[e_tilde]*e_vector^T*e_vectorStarting with expanding out the sum, the using the taylor series equations to prove this
Verify that the exponetial matrix mapping [C] = e^(-phi*[e_tilde])does have the finite form given in this equation:[C] = e^(-phi*[e_tilde]) = [I_3x3]cos(phi) - sin(phi)*[e_tilde]+(1-cos(phi))*e-hat*e-hat^Twhere [e_tilde] and [gamma_tilde] is a skew symmetric matrix and [e_tilde]^3 = -[e_tilde]*e_vector^T*e_vectorStarting with expanding out the sum, the using the taylor series equations to prove this
Related questions
Question
Verify that the exponetial matrix mapping [C] = e^(-phi*[e_tilde])
does have the finite form given in this equation:
[C] = e^(-phi*[e_tilde]) = [I_3x3]cos(phi) - sin(phi)*[e_tilde]+(1-cos(phi))*e-hat*e-hat^T
where [e_tilde] and [gamma_tilde] is a skew symmetric matrix and [e_tilde]^3 = -[e_tilde]*e_vector^T*e_vector
Starting with expanding out the sum, the using the taylor series equations to prove this
Expert Solution

This question has been solved!
Explore an expertly crafted, step-by-step solution for a thorough understanding of key concepts.
Step by step
Solved in 2 steps with 3 images
